Characterization of a Drosophila Alzheimer's disease model: pharmacological rescue of cognitive defects. - Ranjita Chakraborty; Vidya Vepuri; Siddhita D Mhatre; Brie E Paddock; Sean Miller; Sarah J Michelson; Radha Delvadia; Arkit Desai; Marianna Vinokur; David J Melicharek; Suruchi Utreja; Preeti Khandelwal; et al. (PLoS ONE)
Transgenic models of Alzheimer's disease (AD) have made significant contributions to our understanding of AD pathogenesis, and are useful tools in the development of potential therapeutics. The fruit fly, Drosophila melanogaster, provides a genetically tractable, powerful system to study the biochemical, genetic, environmental, and behavioral aspects of complex human diseases, including AD. In an effort to model AD, we over-expressed human APP and BACE genes in the Drosophila central nervous system. Biochemical, neuroanatomical, and behavioral analyses indicate that these flies exhibit aspects of clinical AD neuropathology and symptomology. These include the generation of Aβ(40) and Aβ(42), the presence of amyloid aggregates, dramatic neuroanatomical changes, defects in motor reflex behavior, and defects in memory. In addition, these flies exhibit external morphological abnormalities. Treatment with a γ-secretase inhibitor suppressed these phenotypes. Further, all of these phenotypes are present within the first few days of adult fly life. Taken together these data demonstrate that this transgenic AD model can serve as a powerful tool for the identification of AD therapeutic interventions.